IMMUNOPATHOGENESIS OF DENGUE SHOCK SYNDROME - Sawenda, Karta; Sutirta Yasa, I Wayan Putu; Rasmika Dewi, DAP; Satriyasa, Bagus Komang (Bali Journal of Medical and Health Sciences; vol 1no1 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 D e n g ue is t h e most i m port a n t e me r g i n g tropi ca l vir a l dise a se of hu m a ns in the wo r ld tod a y . I t is e st i m a ted that the r e a re b e tw ee n 50 a nd 100 m i l l ion ca s e s of d e n g u e f e v e r ( D F ) a nd a bout 5 00 . 000 ca s e s o f d e n g ue h ae mor r h a g ic f e v e r ( D H F ) e ac h y e a r whi c h r e quire hospitaliz a t i o n . P e rsons of a ll a g e s ca n be inf ec ted a nd d e v e lop d e n g u e f e v e r. H o w e v e r, c hi l d r e n y ou n g e r than 15 y ea rs t y pic a l l y p re s e nt with on l y a nonsp ec ific s e l f - l i m i ted f e b r i l e i l lness. Untr e a t e d d e n g ue h e mo r rha g ic f e v e r mos t l y l i k e l y pr o g re sses to d e n gue sho c k s y n d rome whi c h is de f ined a s de n g u e fe v e r w i t h s i g ns of c ir c ulato r y f a i l u re . T he p r o g nosis d e p e nds on p re v e nt i on or ea r l y re c o g ni t ion a nd tr ea t m e nt with ca se f a t a l i t y r a te is a s h i g h a s 12% to 14% on c e sho c k h a s s e t i n . Mana g e ment o f d e n g u e f e v e r r e quir e s r e st, o ra l f l uids to c ompens a te f or los s e s via dia r rhoea or vom i t i n g , a n t i p y r e t i c s a nd a n a l g e sic s . P a t i e nts who p r e s e nt wi t h shock m a y r e quire ce nt r a l v e nous p r e ssure mon i tori n g . An ar te r ial l i ne m a y be r e qui r e d in unst a ble p a t i e nts for the a s s e ss me nt of blood g a s e s, e l e c t r o l y te s , a nd c o a g ulation p ro f i l e to h e lp identi f y p a t i e nts n ee di n g v e nt i lato r y support. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}